Optimization of detection of cytomegalovirus viremia in transplantation recipients by shell vial assay. - Patel, R (1995)
Cytomegalovirus (CMV) viremia is a widely used laboratory marker of CMV disease following transplantation and is additionally used to trigger preemptive antiviral therapy. Despite this, the optimal method for diagnosing CMV viremia in transplantation recipients remains unknown. To determine the sampling frequency and blood volume required for the optimal diagnosis of viremia by shell vial assay, a prospective study of 46 viremic transplantation recipients was conducted. Blood specimens (2.5 and 5 ml) were collected twice, 3 h apart, at a median of 1.4 days (range, 1 to 3 days) after the triggering shell vial-positive blood had been collected. Considering a single 2.5-ml specimen, an average of only 40% of previously viremic patients had documented CMV in their blood: this increased to 50% when a second 2.5-ml sample of blood was collected 3 h later. The yields of two 2.5-ml versus two 5-ml samples were 50 versus 61%, respectively. Viremia as detected by shell vial assay is intermittent, and increasing the frequency and volume of blood sampling increases its diagnosis. These results have implications in diagnosis of CMV infection and its preemptive therapy.